2006
DOI: 10.1002/rsa.20158
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrap percolation on the random regular graph

Abstract: ABSTRACT:The k-parameter bootstrap percolation on a graph is a model of an interacting particle system, which can also be viewed as a variant of a cellular automaton growth process with threshold k ≥ 2. At the start, each of the graph vertices is active with probability p and inactive with probability 1 − p, independently of other vertices. Presence of active vertices triggers a bootstrap percolation process controlled by a recursive rule: an active vertex remains active forever, and a currently inactive verte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
165
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(173 citation statements)
references
References 25 publications
(32 reference statements)
7
165
1
Order By: Relevance
“…This result was first proved in [1], see also Theorem 5.1 in [14] which corresponds exactly to our Theorem 4 in this particular setting.…”
Section: Bootstrap Percolation In Random Regular Graphssupporting
confidence: 79%
“…This result was first proved in [1], see also Theorem 5.1 in [14] which corresponds exactly to our Theorem 4 in this particular setting.…”
Section: Bootstrap Percolation In Random Regular Graphssupporting
confidence: 79%
“…Bootstrap percolation on the random regular graph G(n, d) with fixed vertex degree d was studied by Balogh and Pittel [1]. We can recover a large part of their results from Theorem 4.5.…”
Section: Bootstrap Percolation In Random Regular Graphsmentioning
confidence: 57%
“…To be precise, if V (G) = [n] and the elements of A ⊂ V (G) are chosen independently at random, each with probability p, then one aims to determine the value p c of p = p(n) at which percolation becomes likely. Sharp bounds on p c have recently been determined in several cases of particular interest, such as [n] d (see [5,6,7,8,26,27]), on a large family of 'twodimensional' graphs [19], on trees [10,21], and on various types of random graph [11,29]. In each case, it was shown that the critical probability has a sharp threshold.…”
Section: Introductionmentioning
confidence: 99%